Analysis of the Rise of Illegal Parking Attendants and its Impact on Public Service Order and Regional Original Revenue in Sorong City - Yakobus Riry; Karmanis Karmanis; Tri Lestari Hadiati (International Journal of Law and Society, 2026)
This study aims to analyze the prevalence of illegal parking attendants and their impact on public service delivery and the Regional Gross Domestic Product (GDP) in Sorong City. The method used is a mixed-method approach. The study employed quantitative methods, including a questionnaire survey and descriptive statistical analysis, as well as correlation analyses, and qualitative methods, including in-depth interviews and source triangulation. The results indicate that local government oversight, compliance with parking regulations, and the quality of public services are positively and significantly related to increases in local revenue (PAD). Qualitative findings revealed that illegal parking practices lead to revenue leakage, degraded service quality, and public order issues. Consequently, local governments need to strengthen oversight, digitize parking payments, and provide officers with training to increase transparency and optimize local revenue (PAD). The study's limitations lie in its small sample size and its focus on a single location. Future research is recommended to expand the sample, compare several regions, and employ a more comprehensive policy analysis. These results contribute to the development of informal-economy and social-order theory in the context of urban parking management. In practice, the research findings can serve as the basis for formulating more effective and sustainable parking management policies. Implementation of the recommendations is expected to improve the quality of public services and public trust in local governments effectively and sustainably in the future.